Intravenous branched-chain amino acid administration for the acute treatment of hepatic encephalopathy: a systematic review and meta-analysis - Shoji Yokobori; Tomoaki Yatabe; Yutaka Kondo; Yasuhiko Ajimi; Manabu Araki; Norio Chihara; Masao Nagayama; Tetsuya Samkamoto; the Japan Resuscitation Council (JRC) Neuroresuscitation Task Force and the Guidelines Editorial Committee (Journal of Intensive Care)
Abstract Background Hepatic encephalopathy (HE) is a severe complication of acute hepatic failure requiring urgent critical care management. Branched-chain amino acids (BCAAs) such as leucine, isoleucine, and valine have been investigated as potential treatments to improve outcomes in patients with acute HE. However, the effectiveness of BCAA administration during the acute phase remains unclear. This study aimed to evaluate the effect of intravenous BCAA (IV-BCAA) treatment on clinical outcomes in patients with acute HE by systematically reviewing and analyzing randomized controlled trials (RCTs). Methods We conducted a comprehensive literature search of MEDLINE, the Cochrane Central Register of Controlled Trials, and Igaku Chuo Zasshi (ICHUSHI), a Japanese database for medical literature. We included RCTs involving adult patients with acute HE who received IV-BCAA or placebo during the acute phase after admission (< 7 days). Two reviewers independently screened the citations and extracted data. The primary “critical” outcomes were mortality from any cause and improvement in disturbance of consciousness. The secondary “important” outcome included the incidence of complications such as nausea and diarrhea. Risk ratios (RRs) were calculated using random effects models with inverse variance weighting. Results Among the 2073 screened records, four met the criteria for quantitative analysis. The analysis included 219 patients: 109 received IV-BCAA, and 110 received placebo. Improvement in the disturbance of consciousness and mortality were not significantly different between the two groups (RR, 1.26; 95% confidence interval [CI], 0.96–1.66; RR, 0.90; 95% CI 0.70–1.16, respectively). Following IV-BCAA administration, the absolute differences of improvement in the disturbance of consciousness and mortality were 118 more per 1000 (95% CI 18 fewer–300 more) and 55 fewer per 1000 (95% CI 165 fewer–88 more), respectively. No significant differences were observed in the incidence of nausea or diarrhea between the two groups. Conclusions Our meta-analysis demonstrates that all outcomes were not significantly different between IV-BCAA treatment and placebo for acute HE. Further RCTs are required to better understand IV-BCAA treatment potential in patients with HE.